Emerging trends and disparities in cardiovascular, kidney, and diabetes-related mortality: A retrospective analysis of the wide-ranging online data for epidemiologic research database - Aman Goyal; Humza Saeed; Samia Aziz Sulaiman; Wania Sultan; Momina Riaz Siddiqui; Mah I. Kan Changez; Arman Qamar; Sarju Ganatra; Sourbha S. Dani (PLoS ONE, 2025)
Introduction Cardiovascular-kidney-metabolic (CKM) syndrome, driven by metabolic risk factors like obesity, type 2 diabetes (DM-2), chronic kidney disease (CKD), and cardiovascular disease (CVD), leads to poorer health outcomes. Despite its rising prevalence and promising new therapies, trends and demographic disparities in CKM-related mortality among adults in the United States remain underexplored. Methodology The study examined CDC WONDER death certificates for individuals aged 25+ who died from 1999 to 2022, with CVD as the main cause, while CKD and DM-2 as contributing factors. Age-adjusted mortality rates (AAMRs) and annual percent change (APC) were calculated by year, sex, age, race/ethnicity, region, and urbanization status. Results From 1999 to 2022, 25,980 CKM-related deaths were recorded, with the AAMR decreasing from 5.3 to 0.4 per 1,000,000 population. AAMR rose significantly from 1999 to 2012 (APC: 7.03; p<0.001), sharply declined from 2012 to 2015 (APC: -65.55; p<0.001), and then increased from 2015 to 2022 (APC: 15.98; p = 0.101). Men had higher AAMRs than women (6.9 vs. 4.3), and older adults (65+) had the highest AAMR (23.3), followed by middle-aged adults (2.2). Among racial groups, non-Hispanic (NH) American Indian/Alaska Native had the highest AAMR (11.2), followed by NH Black (8.6), Hispanic (6.6), NH White (4.8), and NH Asian/Pacific Islander (4.7). Rural areas showed the highest AAMRs (6.8), compared to medium-small metro (6.1) and large metro areas (4.4). Conclusions CKM-related mortality trends have varied widely over the past two decades, with men, older adults, American Indian/Alaska Native, and non-metropolitan populations experiencing the highest AAMRs, underscoring the need for targeted interventions.